Strategi Meningkatkan Citra Pembelajaran IPS yang Bermakna Menuju Era Society 5.0 - Amini Amini; Azri Syuad Siregar; Nadila Wanti; Siti Safira (Departement of Mathematics Education, 2023)
This study aims to provide information related to relevant strategies which are then empowered to improve the image of social studies learning that is meaningful towards the era of society 5.0. The type of research used is library research, with the following results: (1) Meaningful social studies learning is expected to provide understanding concepts to students in studying and even finding various alternative solutions related to social phenomena and social problems towards the era of society 5.0, for this the teacher's contribution is real in learningIPS needs to be improved as an initial basis towards achieving meaningful learning, (2)Ideally, towards the era of society 5.0, social studies teachers are required to optimize the practice of learning concepts in accordance with the characteristics of the era of society 5.0, (3) use various student-centered learning models (student center learning) actively, innovatively and creatively, empowering information technology-based learning and communication (ICT), and plays an important role in improving the quality of learning by always paying attention to the characteristics of each student collectively.